Retracted article: Khasanov I.F. Modern regional investment policy implementation methods. Statistics and Economics. 2016;(6):114-119. (In Russ.) - article Editorial (Статистика и экономика)
This article by Ildar F. Khasanov has been retracted (i.e. withdrawn from the press) by the editor with permission of the publisher.Retracted article due to unformed borrowings (plagiarism).